The effects of ursodeoxycholic acid on cardiometabolic risk factors: a systematic review and meta-analysis of randomized controlled trials - Elaheh Rashidbeygi; Niloufar Rasaei; Mohammad Reza Amini; Marieh Salavatizadeh; Mehdi Mohammadizadeh; Azita Hekmatdoost (BMC Cardiovascular Disorders)
Abstract Background Chronic diseases such as obesity, hypertension, and metabolic syndrome are major health concerns worldwide. Ursodeoxycholic acid (UDCA) is a bile acid that is naturally produced in the liver and has been used for the treatment of various liver disorders. In this systematic review and meta-analysis, we investigated how UDCA might affect inflammation, blood pressure, and obesity. Methods Five major databases were searched from inception to August 2024. The investigated outcomes included body mass index (BMI), systolic blood pressure (SBP), diastolic blood pressure (DBP), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α). A random effect was carried out to estimate pooled weighted mean difference (WMD) with 95% confidence intervals (CI). The registration code is CRD42023428064. Results Of the 7912 articles in the initial search, 12 were included in the systematic review and meta-analysis. UDCA consumption significantly decreased BMI (WMD: -0.29 kg/m2, 95% CI: -0.58, -0.01, P = 0.044), and DBP (WMD: -2.16 mmHg, 95% CI: -3.66, -0.66, P = 0.005). It also increased SBP (WMD: 5.50 mmHg, 95% CI: 3.65, 7.35, P < 0.001); however, it was not associated with weight loss (WMD: -0.3 kg, 95% CI: -1.3, 0.71, P = 0.561). Our systematic review showed that UDCA consumption has no effect on IL-6 and TNF-α. Conclusion This systematic review and meta-analysis suggest that UDCA supplementation may improve BMI and DBP, whereas it may increase SBP and have no effect on weight or inflammation. Further long-term and well-designed RCTs are needed to further assess and confirm these results.